Perceptions of the family facing the diagnosis and information about chronic disease in childhood - doi: 10.4025/actascihealthsci.v35i2.13691 - Vanessa Medeiros da Nóbrega; Kenya de Lima Silva; Altamira Pereira da Silva Reichert; Simone Elizabete Duarte Coutinho; Neusa Collet (Universidade Estadual de Maringá, 2013)
This study aimed to analyze the perceptions of the family to the diagnosis of chronic disease in childhood; and to assess, from the perspective of the families, the information provided by health professionals. This is a qualitative, descriptive-exploratory study based on the testimonials of families living in João Pessoa, State of Paraíba, whose children had been admitted to a public hospital. The empirical data was produced between November 2008 and January 2009 through participant observation and open interviews. In the analysis, the data were grouped into the following categories: perceptions and feelings of the families on the diagnosis of chronic disease in childhood; and information as a tool for the families deal with the adversities. The results revealed that, despite the long wait, the moment of the final diagnosis is hard and the families need support to overcome the situation and create coping strategies to play their new roles. The family needs to feel safe and confident in its ability to care for the child, which requires information. Shortcomings were verified in the communication between health professionals and family members, especially during hospitalization. The feelings that emerge in the course of chronic illness should not be ignored, but worked together with the family.